ZnFe2O4 nanoparticle-based sensor for 2-butanone detection - Lourenço, Vitor H. [UNESP]; dos S. Theodoro, Reinaldo [UNESP]; de Sá, Bruna S. [UNESP]; Santos, Gustavo S. M. [UNESP]; Perfecto, Tarcísio M.; Volanti, Diogo P. [UNESP] (Springer Nature, 2025)
The advancement in developing and applying gas sensors for detecting microbial volatile organic compounds (MVOCs) is undeniable. Continuous exposure to these compounds can lead to various health problems, including respiratory system damage, gastrointestinal diseases, and mucosal irritation. Additionally, they are linked to environmental harm and food spoilage. Consequently, MVOC sensors are essential for detecting toxic substances in food, enabling non-invasive diagnosis of certain diseases, and monitoring air quality in numerous industrial processes. 2-Butanone is an example of a volatile organic compound that microorganisms, such as Pseudomonas spp., can generate. It is also found in the exhaled breath of individuals diagnosed with lung and ovarian cancer and is frequently associated with the spoilage of beef and other foods. One widely explored approach for producing sensor materials involves using semiconductor metal oxides (SMOx) with metal–organic frameworks (MOFs) as templates. This study presents the synthesis, characterization, and application of ZnFe2O4 nanoparticles derived from ZnFe-MOF as a sensor material. The material was prepared using a mixture of polyvinylpyrrolidone, terephthalic acid, zinc nitrate hexahydrate, iron (III) acetylacetonate, N,N’-dimethylformamide, and ethanol. The synthesis was conducted using the microwave-assisted solvothermal (MAS) method at 150 °C for 2 h and thermal treatment at 450 °C for 2 h. The characterization results demonstrated the formation of ZnFe2O4 nanoparticles with a high degree of purity and an excellent surface area of 81.4 m2/g−1. The ZnFe2O4-based sensor showed good sensitivity to 2-butanone with a response of 63.5 for 100 ppm of this compound at an operational temperature of 300 °C compared to other tested MVOCs (1-pentanol, methanol, benzene, and m-xylene).